The Climate Action Simulation. (April 2020) - Rooney-Varga, Juliette N.; Kapmeier, Florian; Sterman, John D.; Jones, Andrew P.; Putko, Michele; Rath, Kenneth
Background. We describe and provide an initial evaluation of theClimate Action Simulation, a simulation-based role-playing game that enables participants to learn for themselves about the response of theclimate-energy system topotential policies andactions . Participants gain an understanding of the scale and urgency of climate action, the impact of different policies and actions, and the dynamics and interactions of different policy choices. Intervention. The Climate Action Simulation combines an interactive computer model, En-ROADS, with arole-play in which participants make decisions about energy and climate policy. They learn about the dynamics of the climate and energy systems as they discover how En-ROADS responds to their own climate-energy decisions. Methods. We evaluated learning outcomes from the Climate Action Simulation using pre- and post-simulation surveys as well as a focus group. Results. Analysis of survey results showed that the Climate Action Simulation increases participants' knowledge about the scale of emissions reductions and policies and actions needed to address climate change. Their personal and emotional engagement with climate change also grew. Focus group participants were overwhelmingly positive about the Climate Action Simulation, saying it left them feeling empowered to make a positive difference in addressing the climate challenge. Discussion and Conclusions. Initial evaluation results indicate that the Climate Action Simulation offers an engaging experience that delivers gains in knowledge about the climate and energy systems, while also openingaffective andsocial learning pathways.